2020
DOI: 10.1101/2020.03.31.005629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep analysis of the USP18-dependent ISGylome and proteome unveils important roles for USP18 in tumour cell antigenicity and radiosensitivity

Abstract: words)The deubiquitylating enzyme USP18 is a major negative regulator of the interferon (IFN) signalling cascade. IFN pathways contribute to resistance to conventional chemotherapy, radiotherapy, and immunotherapy and are often deregulated in cancer. USP18 is the predominant human protease that cleaves interferon-stimulated gene ISG15, a ubiquitin-like protein tightly regulated in the context of innate immunity, from its modified substrate proteins in vivo. In this study, using advanced proteomic techniques, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…This revealed that about 95% of identified di-Gly-modified peptides in human cells derive from ubiquitylation, rather than neddylation [53], evidence finding that was recently confirmed by global and selective quantification of NEDD8-modified proteins [72]. Since ISGylation appears to be even less frequent and occurs only in response to interferon (IFN)-α/β stimulation [100][101][102][103], K-GG remnant profiling remains a very valuable tool for studying ubiquitin signaling. Kim et al further established that an unexpectedly high fraction of proteins were deubiquitylated after proteasome inhibition, likely reflecting ubiquitin recycling from monoubiquitylated proteins being used for polyubiquitin chain formation on other proteins [104,105].…”
Section: Significance Of Ubiquitinomics In Cell Biology and In Drug D...mentioning
confidence: 92%
“…This revealed that about 95% of identified di-Gly-modified peptides in human cells derive from ubiquitylation, rather than neddylation [53], evidence finding that was recently confirmed by global and selective quantification of NEDD8-modified proteins [72]. Since ISGylation appears to be even less frequent and occurs only in response to interferon (IFN)-α/β stimulation [100][101][102][103], K-GG remnant profiling remains a very valuable tool for studying ubiquitin signaling. Kim et al further established that an unexpectedly high fraction of proteins were deubiquitylated after proteasome inhibition, likely reflecting ubiquitin recycling from monoubiquitylated proteins being used for polyubiquitin chain formation on other proteins [104,105].…”
Section: Significance Of Ubiquitinomics In Cell Biology and In Drug D...mentioning
confidence: 92%
“…The combination of modulating DUB activity with proteomic ubiquitination profiling has been recently applied in other cancer contexts to identify new potential treatment paradigms. For example, Kessler and co-workers used an advanced chemical proteomics approach identify a set of oncogenic substrates of USP18 that appeared to be more susceptible to irradiation, suggesting that selective inhibition of USP18 could sensitise chronic myeloid leukaemia patients to radiotherapy [116]. Practical and robust methods to profile the substrates of UCHL1 across diverse disease contexts will be of great interest to the DUB drug discovery and chemical biology community, for which selective inhibitors such as IMP-1710 will be powerful tools.…”
Section: Future Directions For Uchl1 As a Target In Breast Cancermentioning
confidence: 99%
“…In IFN-treated acute myeloid leukemia cell lines, depletion of USP18 inhibited cell proliferation and induced apoptosis. USP18 -KO cells are sensitive to irradiation-induced apoptosis, suggesting that USP18 is a potential therapeutic target [ 106 ]. Some studies have revealed the molecular mechanisms involved in the USP18-mediated suppression of apoptosis in IFN stimuli.…”
Section: Dubs Regulating Diverse Rcdmentioning
confidence: 99%